Effect of precursors on flavonoid production by Hydrocotyle bonariensis callus tissues - Masoumian, M.; Ariff, Arbakariya; Ahmad, Syahida; Mahmood, Maziah (Academic Journals, 2011)
Callus tissue of Hydrocotyle bonariensis was initiated from the leaf of H. bonariensis treated with 2 mg/l of 2,4-dichlorophenoxyacetic acid (2,4-D) and 1 mg/l kinetin. The culture was kept at 25°C, under light (cool white fluorescent tubes, 1200 lux). To optimize the precursors to increase the production of flavonoid, different precursors were used. The data showed that 4 mg/l proline produced the highest flavonoid yield (10.77 ± 0.25 mg/g DW). The increase in proline concentration did not significantly increase the production of flavonoid. The highest flavonoid yield (10.59 ± 0.18 mg/g DW) was produced in 1 mg/l of glutamine. No significant increase was attained in the flavonoid yield in callus treated with 2, 3 mg/l compared with the control. Phenylalanine at the concentration of 3 mg/l, successfully triggered the production of flavonoid (11.43 ± 0.12 mg/g DW), which was 23% higher than the control. The highest flavonoid production was attained in calluses treated with 4 mg/l of naringenin; and it was 19.72% higher compared with the control.